Enhance state management for high-rise construction activities in Go Vap district, Ho Chi Minh City, Vietnam - Tan, Nguyen Huu; Linh, Le Hoai; Tuong, Le Manh (International Journal of Scientific Research in Civil Engineering, 2022)
The development of high-rise buildings in recent years has posed many difficulties and challenges for localities in the inner space of Ho Chi Minh City such as increasing serious and complicated violations of construction laws, disrupting the planning - architecture of the locality, causing loss to the urban appearance and aesthetics. The number of violation cases in construction order increased due to many objective and subjective reasons. The state management of construction order is still limited, such as: the system of legal documents on construction order is incomplete, sanctions are not deterrent, and there are still violations, lack of responsibility and group benefits, etc